HYDATIFORM MOLE AND ITS MALIGNANT DEGENERATIONS - M. Sarram; M. Fazel; M. Sadeghi (Tehran University of Medical Sciences, 1977)
The result of the 6 years study of patients with Hydatiform Mole (HM) and its malignant degeneration in Isfahan are presented. The over all frequency is estimated to be one HM in 440 child births. This frequency has remained relatively unchanged through out the study. Increased consumption of meet did not seem to lower the frequency of Hydatiform mole in our study. The over all frequency of malignant degeneration was 13.15 percent. The study was divided in two periods of three years. The frequency of malignant trophoblastic disease was compared in these two periods. In the group of patients who referred with HM and were treated in our institution, it was found that the frequency of malignancy was considerably lower during the second three years period (4.27% compared to 27.39%). In contrary the frequency of patients who had their HM treated outside and referred to us with trophoblastic malignancies remained unchanged (7.5% and 5.6%). It is suggested that this improvement is due to earlier diagnosis, and aggressive treatment of Hydatiform mole and also due to more adequate follow up.